2015
DOI: 10.1016/j.pnpbp.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Partial agonism and fast dissociation of LASSBio-579 at dopamine D2 receptor

Abstract: In an attempt to better understand the molecular mechanism of action of the antipsychotic lead LASSBio-579 and of its main metabolite LQFM 037, the aim of this work was to evaluate their intrinsic activity and binding kinetics at the dopamine D2 receptor. In transfected HEK cells expressing the D2L receptor under an inducible promoter, LASSBio-579 and LQFM 037, but not clozapine, behaved as weak partial agonists in [(35)S]-GTPγS binding assays performed in optimized conditions previously shown to evidence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Regarding the ligand-dependent coupling of G i protein, our BRET assay showed that LASSBio-579 and LQFM 037, in a smaller extent, exhibited a (very) weak intrinsic activity. This finding is in agreement with our previous data using a [ 35 S]-GTPγS binding assay and a membrane preparation of Hela Tet-On cells overexpressing the mouse D 2L R. Indeed, we reported that LASSBio-579 and LQFM 037, like aripiprazole but not clozapine, were weak partial agonists of the D 2 R when using such assay, especially in the absence of sodium ions in the incubation medium (Pompeu et al, 2015). These experimental conditions were previously shown to increase the sensitivity to detect weak partial agonists such as aripiprazole, since sodium ions disfavor the formation of the ternary complex of GPCRs (Lin et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the ligand-dependent coupling of G i protein, our BRET assay showed that LASSBio-579 and LQFM 037, in a smaller extent, exhibited a (very) weak intrinsic activity. This finding is in agreement with our previous data using a [ 35 S]-GTPγS binding assay and a membrane preparation of Hela Tet-On cells overexpressing the mouse D 2L R. Indeed, we reported that LASSBio-579 and LQFM 037, like aripiprazole but not clozapine, were weak partial agonists of the D 2 R when using such assay, especially in the absence of sodium ions in the incubation medium (Pompeu et al, 2015). These experimental conditions were previously shown to increase the sensitivity to detect weak partial agonists such as aripiprazole, since sodium ions disfavor the formation of the ternary complex of GPCRs (Lin et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…LASSBio-579 and LQFM 037 also antagonized the effect of dopamine in a concentration-dependent manner, but we were not able to obtain complete inhibition curves due to their lack of solubility at higher concentrations. However, the estimated I max are not maximal, as expected for weak partial agonists, as we observed for blocking of [ 35 S]-GTPγS binding stimulation by dopamine (Pompeu et al, 2015).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation